2001
DOI: 10.1161/hq0701.092137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endurance Exercise Training on Plasma HDL Cholesterol Levels Depend on Levels of Triglycerides

Abstract: Abstract-High density lipoprotein (HDL) cholesterol concentrations have been shown to increase with regular endurance exercise and, therefore, can contribute to a lower risk of coronary heart disease in physically active individuals compared with sedentary subjects. Although low HDL cholesterol levels are frequently observed in combination with hypertriglyceridemia, some individuals may be characterized by isolated hypoalphalipoproteinemia, ie, low HDL cholesterol levels in the absence of elevated triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
4
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(84 citation statements)
references
References 43 publications
(39 reference statements)
7
65
4
8
Order By: Relevance
“…The results of the current study demonstrate that increases in serum triglycerides and total cholesterol caused by leptin receptor deficiency could be decreased significantly by swim training. Our results, in association with those from other researchers, indicate that swim training efficiently regulates triglyceride and cholesterol metabolism in obese mice Couillard et al, 2001;Miyasaka et al, 2003;Savage et al, 2003), and may, therefore, represent an effective means for lowering their levels in blood. In addition, we also observed that training effected a decrease in serum FFA levels, possibly via the restoration of fatty acid oxidation capacity suppressed in db/db mice.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the current study demonstrate that increases in serum triglycerides and total cholesterol caused by leptin receptor deficiency could be decreased significantly by swim training. Our results, in association with those from other researchers, indicate that swim training efficiently regulates triglyceride and cholesterol metabolism in obese mice Couillard et al, 2001;Miyasaka et al, 2003;Savage et al, 2003), and may, therefore, represent an effective means for lowering their levels in blood. In addition, we also observed that training effected a decrease in serum FFA levels, possibly via the restoration of fatty acid oxidation capacity suppressed in db/db mice.…”
Section: Discussionsupporting
confidence: 90%
“…A recent report demonstrated that changes in HMW adiponectin reflect changes in total adiponectin, and that total and HMW adiponectin were equally useful in assessing metabolic risk in patients with coronary artery disease 29) . Previous reports have indicated that exercise training reduces TG and increases HDL-cholesterol 9,10,30) . In particular, greater TG reductions and greater HDLcholesterol elevations after exercise training are often found in previously inactive persons with higher baseline TG levels/lower HDL-cholesterol levels or in patients with impaired glucose tolerance/diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Cholesterol and triglyceride concentrations were determined enzymatically in plasma and lipoprotein fractions using a Technicon RA-500 analyser (Bayer Corporation, Tarrytown, NY, USA) and enzymatic reagents obtained from Randox (Crumlin, UK). Plasma lipoprotein fractions (VLDL, LDL and HDL) were isolated using previously described procedures [36]. Plasma apolipoprotein B (apoB) concentrations were measured by the rocket immuno-electrophoretic method of Laurell [37].…”
Section: Methodsmentioning
confidence: 99%